Akses Pasangan Usia Subur (PUS) Miskin terhadap Informasi Keluarga Berencana (KB) di Kota Yogyakarta - Utami Fitriana Putri; Matahari Ratu; Sugiharti Sri (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2020)
The government’s effort to overcome the high rate of population growth is implementing a family planning program. However, limited access to family planning is undergone by poor population in very great numbers. One factor causing poor couples of childbearing age not to become a family planning acceptor is the limited sources or access to information related to the family planning program. This study aims to find out how poor couples of childbearing age accessed information related to family planning as an initial step to increase family planning acceptors in Yogyakarta. This study used a mixed research method, i.e. quantitative and qualitative designs. Quantitative design was carried out by distributing questionnaires to 368 poor couples of childbearing age selected by using simple random sampling. Qualitative design was carried out with in-depth interviews with six poor couples of childbearing age as well as focus group discussion (FGD) on family planning officers and companions of the Program Keluarga Harapan (PKH) which were selected purposively. The results of this study were analyzed descriptively and content analysis. The majority of poor couples of childbearing age obtained information on contraceptive methods and free family planning program from midwives in primary health care. Delivered information in the form of home visits was only obtained by 7.3% of respondents. The obstacle experienced by family planning officers and PKH companions in delivered family planning information was the assumption that many children have lots of fortune and certain belief factors that prohibit the use of contraception. There was a need for training on interesting educational methods to PKH companion and health cadres to be forwarded to childbearing couples and the existence of media for family planning education as a guide.